A solar cell based on 5-bromo-2-thiophenemethanol organic small molecule interface modification and a preparation method thereof
By introducing 5-bromo-2-thiophene methanol, an organic small molecule interface modifier, into CsPbI2Br perovskite films, the grain boundary defect problem of perovskite films was solved, the stability and efficiency of the devices were improved, and a high-efficiency photoelectric conversion effect was achieved.
Patent Information
- Application Number
- CN202610553408.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-24
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2046-04-24
AI Technical Summary
In perovskite solar cells, CsPbI2Br perovskite films suffer from insufficient cation coordination and excessive grain boundaries, leading to an increase in nonradiative recombination centers of charge carriers and affecting the open-circuit voltage and stability of the device.
5-Bromo-2-thiophene methanol (5B2T) was used as an organic small molecule interface modifier. By forming coordination bonds and hydrogen bonds with CsPbI2Br perovskite films, it passivated grain boundary defects, improved interface energy level matching, suppressed nonradiative recombination loss, and inhibited halide ion migration.
This significantly improves the room-temperature black phase stability and optical stability of CsPbI2Br perovskite films, thereby enhancing photoelectric conversion efficiency and long-term operational stability of the devices.
Smart Images

Figure CN122438459B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of solar energy technology, and in particular to a solar cell based on the interface modification of 5-bromo-2-thiophene methanol organic small molecules and its preparation method. Background Technology
[0002] For many years, perovskite solar cells (PSCs) have been a research hotspot in the photovoltaic field, and due to global advancements in processes and materials, they have achieved rapid growth in power conversion efficiency (PCE). In just over a decade, the cell PCE has increased from 3.8% to 27.3%. However, in mixed perovskites, formamidinium (FA)... + ) and methylamine (MA) + The volatility and thermal instability of cesium (Cs) components have hindered their commercial development. An alternative approach to address this issue is the preparation of inorganic perovskites, CsPbX3 (X: I, Br, or mixed halogens), using cesium (Cs). Among these, CsPbI2Br perovskite exhibits excellent thermal stability, a matched bandgap of 1.9 eV (Eg), and excellent phase stability. However, CsPbI2Br perovskite films prepared via solution methods also suffer from numerous defects, such as insufficient cation coordination and excessive grain boundaries. These defects, acting as nonradiative recombination centers for charge carriers, lead to open-circuit voltage (Voc) losses and severe stability problems. Therefore, extensive research has been conducted to address the defects, including process optimization, additive engineering, interface modification, and size control. Among these optimization techniques, interface modification is considered an effective way to obtain uniform films and reduce defect density.
[0003] This study selected 5-bromo-2-thiophene methanol (5B2T) as a multifunctional organic small molecule modifier to systematically explore its regulatory mechanism on the performance of CsPbI2Br perovskite thin films and devices. On the one hand, 5B2T obtained perovskite thin films with larger grain size and lower defect density by regulating the crystallization process; on the other hand, this additive modulated the energy levels of the perovskite, improved the interfacial energy level matching between the perovskite layer and the charge transport layer, and effectively suppressed nonradiative recombination losses; at the same time, the introduction of 5B2T significantly improved the room temperature black phase stability and optical stability of the film. Based on the above synergistic effects, the photoelectric conversion efficiency of the modified device was significantly improved, and the long-term operational stability was also effectively improved. This multifunctional additive strategy not only provides an effective way to solve the key problems of poor room temperature black phase stability of CsPbI2Br perovskite thin films and low device efficiency, but also opens up new material design ideas for the development of efficient and stable perovskite optoelectronic devices, which is of great significance for promoting the industrial application of clean energy photovoltaic technology. Summary of the Invention
[0004] The purpose of this invention is to provide a solar cell based on the interface modification of the organic small molecule 5-bromo-2-thiophene methanol and its preparation method. By passivating grain boundary defects with 5-bromo-2-thiophene methanol, the quality of CsPbI2Br perovskite thin film is improved, the stability of the perovskite structure is enhanced, thereby improving the photoelectric conversion efficiency and stability of CsPbI2Br perovskite device.
[0005] To achieve the above objectives, this invention provides a solar cell based on the interface modification of the organic small molecule 5-bromo-2-thiophene methanol. The light-absorbing layer of the solar cell is first modified with the organic small molecule 5-bromo-2-thiophene methanol between the light-absorbing layer and the hole transport layer. Through the synergistic effect of coordination bonds and hydrogen bonds between 5-bromo-2-thiophene methanol and the light-absorbing layer, surface defects in the light-absorbing layer are passivated, interfacial non-radiative recombination losses are reduced, halide ion migration in the light-absorbing layer is suppressed, and stability is improved. The light-absorbing layer is CsPbI2Br.
[0006] Its preparation method includes the following steps: An absorber layer is obtained by spin-coating a light-absorbing layer precursor solution onto a substrate with an electron transport layer, followed by annealing. Then, an isopropanol solution of 5-bromo-2-thiophene methanol is spin-coated onto the absorber layer, followed by annealing. Finally, a hole transport layer and an electrode are prepared on the absorber layer.
[0007] Preferably, the 5-bromo-2-thiophene methanol has an average molecular weight of 128.15. The substrate for preparing the electron transport layer is an FTO conductive glass with a planar structure modified SnO2 film coated on its surface. The planar structure modified SnO2 film is preferably a SnO2 film co-modified by ammonium tartrate and nitric acid. Its preparation method is as follows: add an aqueous solution of ammonium tartrate to a SnO2 hydrocolloid dispersion, stir until homogeneous, then add concentrated nitric acid to adjust the pH to 11.50~7.30, stir until homogeneous, filter, and obtain the modified SnO2 precursor solution; spin-coat it onto the substrate, anneal it, and then clean it with ultraviolet ozone. The FTO conductive glass can have a size of 20 mm × 20 mm, a sheet resistance of 14 Ω, and a transmittance ≥90%.
[0008] Preferably, the light-absorbing layer precursor solution is prepared by dissolving CsI, PbI2, and PbBr2 in a dimethyl sulfoxide organic solution. The solution can be dissolved by stirring at a constant temperature of 80℃~120℃ for 0.5~5h, and then filtered through a polytetrafluoroethylene filter after dissolution. The concentration, calculated as Cs, is 1.0~2.0 mol / L.
[0009] Preferably, the concentration of 5-bromo-2-thiophene methanol in the isopropanol solution is 0.8 mg / mL to 1.5 mg / mL.
[0010] This invention reduces film defects and improves room-temperature black phase stability by controlling the amount of 5-bromo-2-thiophene methanol added, providing a feasible approach for preparing high-quality, stable perovskite films. It yields a CsPbI₂Br perovskite device with an optimal PCE of 15.07%, which is of great significance for the research and application of optoelectronic devices. Insufficient modification dosage leads to increased grain boundary defects, poor film crystallinity, and unsatisfactory room-temperature black phase stability and optical stability. Excessive modification dosage causes film stacking, making it uneven, and also increases grain boundary defects, thus affecting the film's optical performance. Only with appropriate modification of 5-bromo-2-thiophene methanol can a CsPbI₂Br perovskite film with optimal performance be obtained. In this invention, the isopropanol solution of 5-bromo-2-thiophene methanol used for spin-coating is 100µL~150µL. CsPbI2Br perovskite films with the addition of an appropriate amount of 5-bromo-2-thiophene methanol exhibit larger grain size, fewer grain boundary defects, dense and smooth texture, and high crystallinity. They also possess good room temperature black phase stability, optical stability, and optical properties.
[0011] Preferably, the spin-coating of the light-absorbing layer precursor solution is performed in stages, including a first stage spin coating and a second stage spin coating. The spin coating speed of the first stage is 500-900 rpm and the spin coating time of the first stage is 10-16 s; the spin coating speed of the second stage is 800-1400 rpm and the spin coating time of the second stage is 80-140 s.
[0012] This invention improves the quality of perovskite films by performing spin coating in stages, thereby enhancing the film's coverage, uniformity, and crystallinity.
[0013] Preferably, the light-absorbing layer obtained by annealing is obtained by gradient annealing, first annealing at a temperature of 50~90 ℃ for 2~8 min; and then annealing at 105~155 ℃ for 1~4 min.
[0014] Preferably, the isopropanol solution of 5-bromo-2-thiophene methanol is spin-coated at a speed of 1000~4000 rpm for 10s~60s; then annealed at 70~110 ℃ for 1~5 min.
[0015] Preferably, after preparing 5-bromo-2-thiophene methanol, 25-75 μL of Spiro-OMeTAD is spin-coated onto it at a spin speed of 2500-4500 rpm for 10-40 s.
[0016] Preferably, an Ag electrode with a thickness of 60-100 nm is deposited on the prepared hole transport layer film.
[0017] This invention improves the quality of perovskite films by employing gradient temperature annealing, thereby increasing film coverage, crystallinity, grain size, and uniformity of size distribution, and reducing defect density.
[0018] This invention introduces a 5-bromo-2-thiophene methanol organic small molecule interface modifier onto the CsPbI2Br perovskite layer, which effectively passivates grain boundary defects and reduces grain boundaries, thereby hindering water penetration and perovskite degradation and promoting uniform grain growth. Therefore, the room-temperature black phase stability and optical stability of the CsPbI2Br film are significantly improved, and the photoelectric conversion efficiency of the device is also enhanced.
[0019] Mechanism of the invention: This invention selects 5-bromo-2-thiophene methanol (5B2T) as an organic small molecule interface modifier, the molecular structure of which is shown below. The S atom of thiophene in 5B2T interacts with the Pb atom in CsPbI2Br. 2+ / Cs + The ions form coordination bonds, passivating interface defects and suppressing nonradiative recombination at the interface. Simultaneously, the H atoms in the -OH group of 5B2T can interact with the I atoms in the CsPbI2Br perovskite via hydrogen bonds. - / Br - Ion interactions inhibit halide ion migration and stabilize the perovskite structure. Furthermore, existing research indicates that the introduction of the -Br group can increase the dipole moment at the top interface, increase the built-in electric field, and improve interfacial hole transport efficiency. The synergistic effect of these groups, coordination bonds, and hydrogen bonds provided by an appropriate amount of the single organic small molecule 5B2T can effectively passivate surface defects in perovskite films, reduce interfacial nonradiative recombination losses, inhibit halide ion migration, and stabilize the perovskite structure, thereby improving device efficiency and stability.
[0020]
[0021] 5-Bromo-2-thiophene methanol molecular structure The beneficial effects of this invention are: (1) The present invention uses FTO conductive glass with a planar structure modified SnO2 film on its surface as a substrate, wherein the planar structure modified SnO2 film has good chemical stability and electrical properties.
[0022] (2) In this invention, 5-bromo-2-thiophene methanol organic small molecule interface modifier is introduced into isopropanol solution to form a composite modification system. This system is beneficial to increase the size of perovskite grains, improve the crystal quality and compactness of the film, reduce the density of grain boundary defects, improve structural stability, and effectively enhance the optical properties of the film.
[0023] (3) The present invention further optimizes the preparation process conditions and parameters so that the prepared CsPbI2Br perovskite thin film has excellent photoelectric properties and is suitable for the field of solar cells.
[0024] (4) The present invention provides a method for improving the performance of perovskite thin films and devices based on 5-bromo-2-thiophene methanol organic small molecule interface modifier. It has the advantages of simple preparation process, low cost and controllable operation, and has important research value and application prospects in the field of perovskite solar cells.
[0025] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0026] Figure 1 These are field emission scanning electron microscope images of Embodiment 1 and Comparative Example 1 of the present invention; Figure 2 These are the X-ray diffraction patterns of Embodiment 1 and Comparative Example 1 of the present invention; Figure 3 These are the UV-Vis absorption spectra of optical stability of Embodiment 1 and Comparative Example 1 of the present invention; Figure 4 These are optical stability diagrams of Embodiment 1 and Comparative Example 1 of the present invention; Figure 5 These are optical photographs of Embodiment 1 and Comparative Example 1 of the present invention; Figure 6 These are the photoluminescence spectra of Embodiment 1 and Comparative Example 1 of the present invention; Figure 7 These are the time-resolved photoluminescence decay curves of Embodiment 1 and Comparative Example 1 of the present invention; Figure 8 These are the 0-2h PL decay curves of Embodiment 1 and Comparative Example 1 of the present invention; Figure 9 These are the Fourier transform infrared spectra of the optimal concentration sample and the modifier sample in Example 1 of this invention; Figure 10 These are the X-ray photoelectron spectroscopy (XPS) spectra of the optimal concentration sample of this invention and Comparative Example 1. Figure 11 This is a diagram illustrating the interaction mechanism between the modifier and CsPbI2Br in this invention; Figure 12 The water contact angle tests were conducted on the modified sample with the optimal concentration of the modifier in Example 1 and the sample in Comparative Example 1. Figure 13 The ultraviolet photoelectron spectroscopy (UPS) test results are obtained from the modified sample with the optimal concentration of the modifier of this invention and the sample in Comparative Example 1. Figure 14These are the JV curves of Embodiment 1 and Comparative Example 1 of the present invention; Figure 15 These are the EQE graphs, Voc and light intensity regression curves, EIS spectra and equivalent circuit diagrams, and PCE statistical graphs of Embodiment 1 and Comparative Example 1 of the present invention. Figure 16 This demonstrates the long-term stability of the efficiency of Embodiment 1 and Comparative Example 1 of the present invention. Detailed Implementation
[0027] Unless otherwise specified, all raw materials used in this invention are commercially available products in the art.
[0028] The present invention will be further described below with reference to the accompanying drawings and embodiments. Unless otherwise defined, the technical or scientific terms used in this invention should have the ordinary meaning understood by one of ordinary skill in the art to which this invention pertains. The features mentioned above or the features mentioned in the specific examples of this invention can be combined arbitrarily, and these specific embodiments are only used to illustrate the invention and are not intended to limit the scope of the invention.
[0029] Example 1 5-Bromo-2-thiophene methanol was dissolved in isopropanol solution to obtain concentration a. i (i=0~5, a0=0<a1=1<a2<a3<a4<a5=5) mg / mL 5-bromo-2-thiophene methanol was heated and stirred at room temperature until completely dissolved to obtain a mixture. 125 μL of the mixture was dropwise added to an FTO / modified SnO2 / CsPbI2Br film substrate treated with UV ozone and spin-coated at 3000 rpm for 30 s. Annealing was then performed at 80℃ for 2 min to obtain the FTO / modified SnO2 / CsPbI2Br / 5B2T film. 50 μL of Spiro-OmeTAD was spin-coated onto the prepared FTO / modified SnO2 / CsPbI2Br / 5B2T thin film at a spin-coating speed of 3000 rpm for 30 s. An Ag electrode was then deposited under vacuum to obtain a perovskite solar cell with the device structure of FTO / modified SnO2 / CsPbI2Br / 5B2T / Spiro-OmeTAD / Ag.
[0030] Comparative Example 1 Based on Example 1, the difference from Example 1 is that 5-bromo-2-thiophene methanol is not modified, and all other aspects are the same as in Example 1.
[0031] Characterization experiments were performed on the CsPbI₂Br perovskite thin films and devices prepared in Example 1 and Comparative Example 1. In Example 1, a₁wt% is denoted as CsPbI₂Br-5B₂T, and in Comparative Example 1, it is denoted as CsPbI₂Br. The following is a detailed description with reference to the accompanying drawings: Figure 1 These are field emission scanning electron microscope images of Embodiment 1 and Comparative Example 1 of the present invention. Figure 1 Images (a)–(f) are FESEM images of CsPbI₂Br perovskite films modified with different concentrations of 5-bromo-2-thiophene methanol (5B₂T) (a₀–a₅ mg / mL). Figure 1 As can be seen in (a), the unmodified film surface has small grains, with a grain size of 597.97 nm, and exhibits pinholes and grain boundary defects, resulting in poor crystallinity. Figure 1 As shown in (b), the CsPbI2Br perovskite film modified with 1 mg / mL 5B2T is smooth and dense, with increased grain size (763.59 nm), reduced grain boundary defects, and improved grain boundary clarity, indicating a significant improvement in crystallinity. However, from... Figure 1 As shown in (b)-(f), with the 5B2T concentration increasing from a1 mg / mL to a5 mg / mL, the grain size decreased to varying degrees, from 763.59 nm to 376.72 nm. Local unevenness and blurred grain boundaries gradually appeared on the film surface, and the CsPbI2Br films modified with a5 mg / mL 5B2T exhibited stacking. This may be because excessive modifier interfered with the normal nucleation and growth process of the crystals, thus reducing the crystallinity of the film and introducing more defects. These results indicate that a1 mg / mL is the optimal concentration of 5B2T for modifying CsPbI2Br perovskite films, which helps to obtain better film quality. Cross-sectional SEM images are shown below. Figure 1 As shown in (g)-(h), the 5B2T interface modification layer is located between the CsPbI2Br layer and the Spiro-OMeTAD layer.
[0032] Figure 2The X-ray diffraction patterns are of CsPbI2Br perovskite films without 5B2T in Comparative Example 1 and those modified with different concentrations of 5B2T in Example 1. The diffraction peaks at 14.9°, 20.9°, and 29.5° correspond to the (100), (110), and (200) crystal planes of the α-phase CsPbI2Br perovskite, respectively. As the concentration of the 5B2T modifier increases from a0 mg / mL to a1 mg / mL, the intensity of the diffraction peaks corresponding to the (100) and (200) crystal planes increases significantly, especially. When the concentration of the 5B2T modifier increases from a1 mg / mL to a5 mg / mL, the intensity of the diffraction peaks corresponding to the (100) and (200) crystal planes of the CsPbI2Br perovskite film modified with a1 mg / mL 5B2T reaches its maximum value, indicating that the perovskite film modified with a1 mg / mL 5B2T has the best crystallinity. The improved crystallinity of CsPbI₂Br films is mainly attributed to two factors. First, the modifier molecules may adsorb onto the surface of CsPbI₂Br crystals, providing additional nucleation sites and thus promoting crystal growth. Second, the introduction of 5B₂T may help improve the structural order of the film. As the modifier concentration further increased from a₁ mg / mL to a₅ mg / mL, the diffraction peaks corresponding to the α-phase CsPbI₂Br (100), (110), and (200) crystal planes gradually decreased. This indicates that excessively high concentrations of 5B₂T modifier may introduce unfavorable interfacial stresses and defects, disrupting lattice order. Therefore, an appropriate amount of interfacial modifier helps improve the crystallinity of the film.
[0033] Figure 3 This table shows the UV-Vis absorption spectra of CsPbI₂Br films modified with different concentrations of 5B₂T in Example 1 of this invention from 0 to 90 min. Table 1 shows the absorption edge cutoff wavelength and band gap values corresponding to the UV-Vis absorption spectra of CsPbI₂Br perovskite films modified with different concentrations of 5B₂T. Figure 3As shown in Table 1, the band gap of the CsPbI2Br perovskite films modified with 5B2T at concentrations of a0-a5 mg / mL is within the range of 1.893 eV to 1.903 eV. In the wavelength range of 500 nm to 800 nm, as the concentration of the 5B2T modifier increases from a0 mg / mL to a1 mg / mL, the absorption edge of the perovskite film redshifts from 653.67 nm to 654.78 nm, the band gap decreases from 1.896 eV to 1.893 eV, and the absorbance increases accordingly. Conversely, as the concentration of the 5B2T modifier increases from a1 mg / mL to a5 mg / mL, the absorption edge of the perovskite film blueshifts from 654.78 nm to 651.57 nm, the band gap increases from 1.893 eV to 1.903 eV, and the absorbance decreases accordingly. Experimental results show that the CsPbI2Br perovskite film modified with 1 mg / mL 5B2T exhibits the best light absorption performance in the 500 nm-800 nm wavelength range.
[0034] Table 1
[0035] Figure 4 The fluorescence spectra of CsPbI₂Br films in Comparative Example 1 (without 5B₂T) and Example 1 (with different concentrations of 5B₂T) are shown. To evaluate the effect of different concentrations of 5B₂T modifier on the optical stability of CsPbI₂Br perovskite films, we performed UV-Vis absorption spectroscopy measurements on CsPbI₂Br films modified with different concentrations of 5B₂T at 20 °C and 45% RH, within 0–90 min at 10 min intervals. Figure 4As shown in the figure. The results indicate that, within the wavelength range of 500 nm to 800 nm, the absorbance of the CsPbI₂Br sample gradually decreases as the testing time increases from 0 min to 90 min. Compared with the unmodified CsPbI₂Br film, the CsPbI₂Br film sample modified with a₁ mg / mL 5B₂T exhibits the smallest change in absorbance within the 0–90 min range and can maintain the 650 nm characteristic absorption edge of CsPbI₂Br for a longer period of time. As the concentration increased from a1 mg / mL to a5 mg / mL, the absorbance of the CsPbI2Br film modified with a2 mg / mL 5B2T was significantly lower than that of the unmodified and a1 mg / mL modified samples at 40 min. The absorbance of the a3 mg / mL 5B2T modified sample decreased significantly at 40 min, but maintained good absorbance intensity at 90 min. The absorbance intensity of the a4 mg / mL 5B2T modified sample decreased significantly at 50 min, failing to meet the 650 nm characteristic absorption edge of CsPbI2Br, indicating sample decomposition. The absorbance of the a5 mg / mL 5B2T modified sample decreased at 20 min, indicating the beginning of sample decomposition. These results confirm that a1 mg / mL 5B2T significantly improves the optical stability of the CsPbI2Br film. Furthermore, we characterized the room temperature black phase stability of the samples.
[0036] Figure 5 Optical photographs of CsPbI2Br perovskite films modified with different concentrations of 5B2T in Example 1, taken after storage at 20°C and RH 45% for 0-90 minutes. Figure 5 As shown, the film sample modified with a1 mg / mL 5B2T remained uniformly black from 0 to 90 min, without any significant color change. In contrast, the unmodified sample gradually turned white at the corners as the testing time increased, and the black color began to fade after 80 min, with the sample showing a slight whitening, indicating slight degradation of the perovskite. The a2 mg / mL modified sample showed whitening at the edges around the perimeter at 40 min, indicating slight decomposition of the perovskite. The a3 mg / mL modified sample showed a slight whitening at the right edge at 40 min, indicating the beginning of degradation. The a4 mg / mL modified sample showed fading black color and whitening around the edges at 50 min, indicating decomposition. The a5 mg / mL modified sample showed white streaks on the upper half of the film at 20 min, indicating the beginning of decomposition. These results confirm that the introduction of a1 mg / mL 5B2T significantly improved the room-temperature black phase stability of the CsPbI2Br film.
[0037] Figure 6 The images show the photoluminescence (PL) spectra of CsPbI₂Br films modified with different concentrations of 5B₂T in Example 1 at an excitation wavelength of 375 nm. Figure 6As can be seen, the emission peak positions of all samples are around 660 nm. When the concentration of 5B2T modifier increases from a0 mg / mL to a1 mg / mL, the emission peak intensity of the film reaches its maximum; as the concentration of 5B2T modifier further increases from a1 mg / mL to a5 mg / mL, the emission peak intensity of the film gradually decreases. The results indicate that the 5B2T modified CsPbI2Br film at a1 mg / mL has the lowest defect concentration, the most significant defect passivation effect, and the most obvious ion migration inhibition effect.
[0038] Figure 7 The time-resolved photoluminescence (TRPL) decay curves of the CsPbI₂Br films modified in Example 1 and Comparative Example 1 are shown in Table 2. The corresponding decay kinetic fitting parameters are summarized in Table 2. As shown in Table 2, the average carrier lifetime (τ) of the CsPbI₂Br perovskite film modified with a₁ mg / mL 5B₂T is... ave The mean carrier lifetime (τ) is 0.41 ns, which is longer than the mean carrier lifetime (τ) of the unmodified CsPbI2Br film. ave (0.36 ns). This result indicates that a1 mg / mL 5B2T modification effectively passivates defect states in perovskite films, suppresses ion migration and nonradiative recombination processes, thereby extending the lifetime of photogenerated carriers.
[0039] Table 2
[0040] Figure 8 The CsPbI₂Br films modified in Example 1 and Comparative Example 1 both exhibited similar photoluminescence (PL) emission peaks at approximately 660 nm in their initial state when excited at a wavelength of 375 nm. Figure 8 As can be seen, at 20℃ and 45% RH, with the illumination time increasing from 0h to 2h, the intensity of the PL emission peak of the 0 mg / mL 5B2T modified film significantly decreased, and its peak position exhibited a slight redshift, moving from 663.50 nm to 665.91 nm. In contrast, Figure 8 The intensity of the PL emission peak of the a1 mg / mL 5B2T modified film showed almost no decrease within 0–2 h, and its spectral curves maintained a high degree of overlap within the same timeframe. These results indicate that the a1 mg / mL 5B2T modification layer effectively suppressed CsPbI2Br ion migration and phase separation processes, thereby improving the room-temperature phase stability of the CsPbI2Br film.
[0041] like Figure 9 As shown, we further explored the interaction mechanism between 5B2T and CsPbI2Br using Fourier transform infrared spectroscopy (FTIR). Figure 9The tensile vibration peak of -OH in 5B2T appears at 1351 cm⁻¹. -1 The stretching vibration peak of -OH in CsPbI2Br-a1mg / mL 5B2T shifted to 1325 cm⁻¹. -1 Furthermore, its intensity was significantly weakened, indicating that the -OH group in the modifier 5B2T interacted with CsPbI2Br; in addition, the CS tensile vibration peak in 5B2T appeared at 1430 cm⁻¹. -1 At 1425 cm⁻¹, the tensile vibration peak of CS in CsPbI₂Br⁻⁵B₂T shifted to 1425 cm⁻¹. -1 Furthermore, its intensity significantly decreased, indicating that CS in the modifier 5B2T interacted with CsPbI2Br. The interaction between 5B2T and CsPbI2Br can, on the one hand, improve the room-temperature black phase stability of perovskites. On the other hand, it can effectively passivate perovskite defects, thereby inhibiting ion migration and reducing non-radiative recombination losses.
[0042] To further understand the interaction mechanism between 5B2T and CsPbI2Br, we performed X-ray photoelectron spectroscopy (XPS) characterization. Figure 10 Images (a)-(d) show the XPS spectra of a pure CsPbI₂Br film and an a₁ mg / mL 5B₂T modified CsPbI₂Br perovskite film. Figure 10 As shown in (a), the characteristic peaks of Pb 4f 5 / 2 and Pb 4f7 / 2 in the pure CsPbI2Br film appear at 137.70 eV and 142.52 eV, respectively; while the characteristic peaks of Pb 4f5 / 2 and Pb 4f7 / 2 in the CsPbI2Br perovskite film modified with the optimal concentration of 5B2T shift to binding energies of 137.47 eV and 142.36 eV, respectively. The shift of the characteristic peaks of Pb 4f5 / 2 and Pb 4f7 / 2 in the CsPbI2Br-5B2T perovskite film towards lower binding energies indicates that 5B2T may bind with uncoordinated Pb in CsPbI2Br. 2+ Coordination occurs. (By...) Figure 10As shown in (b), the XPS spectra of Cs 3d in the CsPbI2Br film exhibit characteristic peaks for Cs 3d 3 / 2 and Cs 3d 5 / 2 at binding energies of 737.68 eV and 723.74 eV, respectively. However, the characteristic peaks for Cs 3d 3 / 2 and Cs 3d 5 / 2 in the CsPbI2Br-a1mg / mL 5B2T perovskite film shift to binding energies of 737.57 eV and 723.45 eV, respectively. After modification with a1mg / mL 5B2T, the characteristic peaks of Cs 3d 3 / 2 and Cs 3d 5 / 2 in the perovskite film shift towards lower binding energies, indicating that 5B2T may interact with uncoordinated Cs 3d 3 / 2 ions in CsPbI2Br. + Coordination. Combined with FTIR spectroscopy results, it can be inferred that the S atom in the thiophene of 5B₂T may coordinate with the Pb atom in CsPbI₂Br. 2+ / Cs + Coordination occurred, effectively passivating defects and suppressing nonradiative recombination of charge carriers. For example... Figure 10 As shown in (c), the XPS spectrum of Br 3d in the pure CsPbI₂Br film shows that the characteristic peak of Br 3d is located at 67.74 eV. In the CsPbI₂Br perovskite film modified with 1 mg / mL 5B₂T, the characteristic peak of Br 3d shifts towards a lower binding energy (67.45 eV). Figure 10 As shown in (d), the characteristic peaks I3d 5 / 2 and I3d 3 / 2 corresponding to the pure CsPbI2Br film are at 629.80 eV and 618.28 eV, respectively. However, the characteristic peaks I3d corresponding to the CsPbI2Br perovskite film modified with 1 mg / mL 5B2T shift towards lower binding energies, reaching binding energies of 629.61 eV and 618.16 eV, respectively. The experiment shows that 5B2T binds to the Br in CsPbI2Br perovskite. - and I - A bond has formed. Combined with FTIR spectroscopy results, it can be seen that the H atom in the -OH group of 5B₂T binds to the Br atom in CsPbI₂Br. - and I - Hydrogen bonds exist between them, effectively preventing the migration of halide ions and stabilizing the perovskite structure.
[0043] Based on the analysis results of FTIR and XPS spectra, we can derive the bonding mechanism diagram between 5B2T and CsPbI2Br, as follows: Figure 11 As shown. From Figure 11 It can be seen that the S atom in thiophene in 5B2T and the Pb atom in CsPbI2Br are related. 2+ / Cs+ The ions form coordination bonds, passivating interface defects and suppressing nonradiative recombination at the interface. Furthermore, the H atom in the -OH group of 5B2T can interact with the I atom in the all-inorganic CsPbI2Br perovskite via hydrogen bonds. - / Br - Ion interactions inhibit halide ion migration and stabilize the perovskite structure. The synergistic effect of coordination bonds and hydrogen bonds passivates surface defects in the perovskite film, reducing interfacial nonradiative recombination losses; it also inhibits halide ion migration and improves the stability of the perovskite structure.
[0044] To evaluate the effect of the optimal concentration of 5B2T modification on the hydrophobicity of CsPbI2Br membranes, we conducted water contact angle tests on the CsPbI2Br membranes modified in Example 1 and Comparative Example 1. Figure 12 Tables (a) and (b) show the water contact angles of the CsPbI2Br films modified in Example 1 and Comparative Example 1, respectively. Figure 12 As can be seen, after modification with 1 mg / mL 5B2T, the water contact angle of the perovskite film increased from 29.9° to 73.9°. This is mainly due to the hydrophobicity of the thiophene ring and bromine substituent in the 5B2T modifier, which can prevent water from penetrating and diffusing into the perovskite grain boundaries, effectively improving the moisture resistance of the perovskite, and thus helping to improve the long-term stability of the CsPbI2Br film in a humid environment.
[0045] To investigate the effect of 5B2T top interface modification on the energy level alignment of CsPbI2Br PSCs, we performed ultraviolet photoelectron spectroscopy (UPS) tests on the CsPbI2Br samples modified in Example 1 and Comparative Example 1, and obtained... Figure 13 The cutoff edge (E) in (a) cutoff )and Figure 13 The starting edge (E) of (b) onset The results, along with the band structure parameters, are shown in Table 3. Furthermore, we... Figure 13 The corresponding energy level diagram is plotted in (c), which more intuitively shows the effect of a1 mg / mL 5B2T modification on the energy levels of perovskite materials. Through analysis... Figure 13 The UPS spectrum shown in (c) and the E of the thin film cutoff Maximum valence band energy (VBM) and E onset We use formula E VBM = 21.22-(E cutoff -E onset Calculate the Ei of pure CsPbI2Br and a1 mg / mL 5B2T modified CsPbI2Br. VBM The values are -5.93 eV and -5.63 eV, respectively. Using E...VBM and E CBM These values are used to plot the energy levels of PSCs (see...). Figure 13 (c)). From Figure 13 As shown in (c), after modification with 1 mg / mL 5B2T, the CsPbI2Br film exhibits a significant upward shift in VBM, resulting in a 0.30 eV reduction in the energy level difference between the perovskite layer and HTL. This favorable interface energy level difference optimization indicates that 5B2T interface modification can regulate the energy level mismatch between the perovskite layer and HTL, thereby promoting the transfer and extraction of photogenerated holes and ultimately improving device performance.
[0046] Table 3
[0047] To investigate the effect of 5B2T interface modifier concentration on the photovoltaic performance of CsPbI2Br perovskite solar cell devices (PSCs), we fabricated PSCs with the structure FTO / (AT+HNO3)-SnO2 / CsPbI2Br / 5B2T / Spiro-OMeTAD / Ag. Figure 14 The JV curves of CsPbI2Br PSCs modified with different concentrations of 5B2T in Example 1 are shown under test conditions of 20℃ and 45% RH, with an effective device area of 0.06 cm². 2 The corresponding photovoltaic parameters are shown in Table 4. From... Figure 14 As shown in Table 4, when the concentration of 5B2T increases from a0 mg / mL to a1 mg / mL, V OC From 0.96 V to 1.07 V, J SC From 20.53mA / cm 2 Rising to 23.85 mA / cm 2 FF increased from 0.59 to 0.61, and PCE increased from 12.21% to 14.61%. However, as the 5B2T concentration increased from a1 mg / mL to a5 mg / mL, V... OC From 1.07 V to 0.87 V, J SC From 23.85mA / cm 2 It dropped to 16.56 mA / cm 2 The FF decreased from 0.61 to 0.38, and the PCE decreased from 14.61% to 5.39%. The results indicate that the optimal concentration of a1 mg / mL 5B2T for interface modification significantly improved the VF of the CsPbI2Br perovskite solar cell. OC J SCThe addition of FF ultimately improved PCE. The optimal concentration of 1 mg / mL 5B2T-modified CsPbI2Br PSCs exhibited the best photovoltaic performance.
[0048] Table 4
[0049] Figure 15 (a) shows the external quantum efficiency (EQE) of the CsPbI₂Br PSCs modified in Comparative Example 1 and Example 1, tested at 20 °C and 55% RH. The pure CsPbI₂Br device exhibits the highest EQE value of 80.21%, with a calculated integral current of 19.46 mA / cm². 2 , and JV test J sc Approximately (20.53 mA cm) -2 The device modified with 1 mg / mL 5B2T achieved a maximum EQE value of 87.69% and a corresponding mA / cm² performance. 2 The integral current is basically consistent with the Jsc measured by JV (23.85 mA / cm). 2 Analysis of the EQE test results clearly shows that a1 mg / mL 5B2T modification significantly improves the EQE value of CsPbI2Br perovskite solar cells. This indicates that a1 mg / mL 5B2T modification helps improve the quantum conversion efficiency of the device, thereby improving the photoelectric conversion efficiency of the device.
[0050] To evaluate the efficiency loss mechanism of perovskite solar cells, this study compared and tested the open-circuit voltage (Voc) of unmodified and modified CsPbI2Br devices with a1 mg / mL 5B2T under different light intensities at 20℃ and 45% RH. Figure 15 As shown in (b). Through analysis of V oc The relationship between light intensity and the device can effectively assess the charge recombination behavior caused by interface defects. The results show that, compared to the unmodified reference device, the device modified with a1 mg / mL 5B2T exhibits lower Vc at all light intensities. oc Loss. V oc The relationship between V and light intensity (I) can be expressed as V oc=nkTln(I) / q, where n is the ideality factor of illumination, k is the Boltzmann constant, T is the temperature, and q is the elementary charge. Ideally, when carriers in the device only diffuse and do not recombine, n = 1; while n > 1 indicates trap-assisted nonradiative recombination. Experimentally, the n value for the unmodified device was measured to be 1.93 (k1 = 1.93 kT / q, n1 = 1.93), while the n value for the a1 mg / mL 5B2T modified device decreased to 1.58 (k1 = 1.58 kT / q, n2 = 1.58). The decrease in the ideality factor of illumination indicates that a1 mg / mL 5B2T modification can improve device performance by passivating defects, thereby suppressing ion migration, reducing nonradiative recombination losses, and thus improving device performance.
[0051] To investigate the effect of optimal 5B₂T concentration at the top interface on charge transport and recombination processes in CsPbI₂Br perovskite solar cells, we measured the EIS spectra and equivalent circuit diagrams of CsPbI₂Br and a1 mg / mL 5B₂T-CsPbI₂Br perovskite solar cells under ambient conditions of 20 °C and 45% RH. Figure 15 As shown in (c), the relevant parameters obtained from the fitting are shown in Table 5. The results indicate that the optimal concentration of a1 mg / mL 5B2T-modified device has the highest charge transport impedance (R0). trans The RΩ was 316.4 Ω, significantly lower than the unmodified control group (478.3 Ω). The lower RΩ trans The value typically reflects a more efficient charge transport capability and better charge conductivity, thereby increasing the short-circuit current density (J / mL) of the a1 mg / mL 5B2T modified device. sc 20.53 mA / cm for unmodified devices 2 Increased to 23.85 mA / cm 2 .
[0052] To verify reproducibility, we fabricated 16 individual CsPbI₂Br and a₁mg / mL 5B₂T-CsPbI₂Br PSCs devices, respectively, and plotted PCE statistical box plots, as shown below. Figure 15 As shown in Figure (d), the photovoltaic performance parameters are presented in Table 6. Experimental results show that the PCE parameter distribution of the CsPbI₂Br perovskite solar cell modified with the optimal concentration a₁mg / mL 5B₂T is denser than that of the pure device. This indicates that CsPbI₂Br-a₁mg / mL 5B₂T PSCs have better PCE reproducibility than CsPbI₂Br PSCs.
[0053] Table 5
[0054] Table 6
[0055] Figure 16 The results show the stability of the power conversion efficiency (PCE) of CsPbI2Br solar cells modified with different concentrations of 5B2T under ambient conditions of 20℃ and 45% RH. Figure 16 As shown, top interface modification with a1 mg / mL 5B2T improves the air stability of the device. The CsPbI2Br solar cell modified with a1 mg / mL 5B2T retains approximately 74.14% of its initial PCE after 60 days of storage at 20 °C and 45% relative humidity, while the pure CsPbI2Br solar cell retains only approximately 59.78% of its initial PCE. This enhanced PCE stability can be mainly attributed to the interaction between the S atom in thiophene in 5B2T and the Pb atom in CsPbI2Br. 2+ / Cs + Coordination between ions, and the interaction between the H atom in the -OH group of 5B2T and the Br atom in perovskite. - / I - Hydrogen bonding between the perovskite ions effectively inhibits the migration of halide ions, enhances the structural stability of the perovskite material, and thus significantly improves the long-term stability of the device in air.
[0056] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. A solar cell based on the interface modification of 5-bromo-2-thiophene methanol organic small molecules, characterized in that, In a solar cell, the light-absorbing layer is first modified with the organic small molecule 5-bromo-2-thiophene methanol, which is CsPbI2Br. The surface defects of the light-absorbing layer are passivated by the synergistic effect of coordination bonds and hydrogen bonds between 5-bromo-2-thiophene methanol and the light-absorbing layer CsPbI2Br, thereby reducing interfacial nonradiative recombination losses, inhibiting the migration of halide ions in the light-absorbing layer, and improving stability.
2. The method for preparing a solar cell based on the interface modification of 5-bromo-2-thiophene methanol organic small molecules as described in claim 1, characterized in that, include: An absorber layer is obtained by spin-coating a light-absorbing layer precursor solution onto a substrate with an electron transport layer, followed by annealing. Then, an isopropanol solution of 5-bromo-2-thiophene methanol is spin-coated onto the absorber layer, followed by annealing. Finally, a hole transport layer and an electrode are prepared on the absorber layer.
3. The method for preparing a solar cell based on the interface modification of 5-bromo-2-thiophene methanol organic small molecules according to claim 2, characterized in that, The substrate on which the electron transport layer is prepared is a conductive glass with a planar structure modified SnO2 film covering its surface. The planar structure modified SnO2 film is a SnO2 film synergistically modified with ammonium tartrate and nitric acid.
4. The method for preparing a solar cell based on the interface modification of 5-bromo-2-thiophene methanol organic small molecules according to claim 2, characterized in that, The light-absorbing layer precursor solution is prepared by dissolving CsI, PbI2, and PbBr2 in a dimethyl sulfoxide organic solution, and its concentration, calculated as Cs, is 1.0–2.0 mol / L.
5. The method for preparing a solar cell based on the interface modification of 5-bromo-2-thiophene methanol organic small molecules according to claim 2, characterized in that, The precursor solution for spin-coating the light-absorbing layer is spin-coated in stages, including a first-stage spin-coating and a second-stage spin-coating. The spin-coating speed for the first stage is 500–900 rpm and the time is 10–16 s. The spin-coating speed for the second stage is 800–1400 rpm and the time is 80–140 s.
6. The method for preparing a solar cell based on the interface modification of 5-bromo-2-thiophene methanol organic small molecules according to claim 2, characterized in that, The light-absorbing layer obtained by annealing growth is obtained by gradient annealing, first annealing at a temperature of 50~90℃ for 2~8 min; and then annealing at 105~155℃ for 1~6 min.
7. The method for preparing a solar cell based on the interface modification of 5-bromo-2-thiophene methanol organic small molecules according to claim 2, characterized in that, The concentration of 5-bromo-2-thiophene methanol in the isopropanol solution is 0.8 mg / mL to 1.5 mg / mL.
8. The method for preparing a solar cell based on the interface modification of 5-bromo-2-thiophene methanol organic small molecules according to claim 2, characterized in that, The volume of the isopropanol solution of 5-bromo-2-thiophene methanol used for spin coating is 100µL~150µL.
9. The method for preparing a solar cell based on the interface modification of 5-bromo-2-thiophene methanol organic small molecules according to claim 2, characterized in that, Spin-coating of 5-bromo-2-thiophene methanol in isopropanol solution at a spin speed of 1000–4000 rpm for 10–60 s; annealing temperature of 70℃–110℃; annealing time of 1 min–5 min.
10. The method for preparing a solar cell based on the interface modification of 5-bromo-2-thiophene methanol organic small molecules according to claim 2, characterized in that, The hole transport layer is Spiro-OMeTAD, and the electrode is Ag with a thickness of 60~100nm.
Citation Information
Patent Citations
Interface modification method of all-inorganic perovskite thin film and thin film
CN115697000A
Organic molecular additive as well as preparation method and application thereof
CN118146210A
